A Combination of Prebiotic Inulin and Oligofructose Improve Some of Cardiovascular Disease Risk Factors in Women with Type 2 Diabetes: A Randomized Controlled Clinical Trial - Aliasgharzadeh, Akbar (Adv Pharm Bull, 2015)
Purpose: This trial was conducted to evaluate the effects of oligofructose-enriched inulin on some of cardiovascular disease risk factors in women with type 2 diabetes. Methods: 52 females (25<BMI<35 kg/m2) with type 2 diabetes were randomly assigned to two groups. Participants received 10g/d oligofructose-enriched inulin (n=27) or 10g/d placebo (n=25) for 8 weeks. Fasting blood samples were taken to measure metabolic profiles, malondialdehyd and antioxidant enzymes at baseline and after the 8 weeks intervention. Paired, unpaired sample t-test and analysis of covariance were used to comparison of quantitative variables. Results: After 8 weeks, in the oligofructose-enriched inulin group there was a significant increase in total antioxidant capacity (0.2 mmol/l, 20.0%) and a significant decrease in fasting plasma glucose (19.2 mg/dL, 9.4%) HbA1c (0.5%, 8.4%), total cholesterol (TC) (28.0 mg/dL, 14.1%), low-density lipoprotein cholesterol (LDL-c) (22.0 mg/dL, 21.7%), TC/HDL-c ratio (0.73, 20.7%), LDL-c/HDL-c ratio (0.55, 27.5%) and malondialdehyd (1.7 nmol/ml, 39.7%) compared to the placebo group. Changes in concentrations of triglycerides, high-density lipoprotein cholesterol (HDLc), superoxide dismutase, catalase and glutathione peroxidase were not significant in oligofructose-enriched inulin group compared to the placebo group. Conclusion: Oligofructose-enriched inulin may improve glycemic indices, lipid profile, antioxidant status and malondialdehyd in women with type 2 diabetes.